Comparative phytochemical analysis and antioxidant activities of two herbal powdered drugs used in the treatment of uterine fibroids - Karunagoda, K.P.K.R.; Perera, P.K.; Senanayake, H. (Asian Journal of Pharmacognosy, 2020)
Nigella sativa Linn (Family: Ranunculaceae) and Anethum sowa Linn (Family: Apiaceae) are commonly used herbs in Ayurveda medicine from ancient times highlighting its’ use in the treatment of uterine fibroids throughout the island in Sri Lanka. Uterine fibroids are the most common benign tumor of the female reproductive tract and occur in about 25% of all women of reproductive age and up to 30 – 40% of women over age 40. N. sativa and A. sowa are used in Sri Lanka for the treatment of uterine fibroids and other common gynecological disorders from ancient days. The phytochemical analysis was carried out by Thin Layer Chromatography and Gas Chromatography analysis. Besides, DPPH scavenging ability, total phenol, and total flavonoid contents were compared. The TLC fingerprints of N. sativa and A. sowa were prominent and can be used as standards for the authentication of these plants. The DPPH free radical scavenging activity was significantly higher in A. sowa than that of N. sativa. Moreover, total polyphenol and flavonoid contents were significantly higher in A. sowa than that of N. sativa. A. sowa showed comparatively more antioxidant activities than that of N. sativa and may use for treating uterine fibroids due to the presence of higher polyphenols and flavonoid types of compounds.
Keywords: Phytochemical Analysis; Antioxidant Activities; Nigella sativa L; Anethum sowa L